Pelatihan Kepemimpinan Bagi Pengurus OSIS Di MA Daruttaqwa Gresik - Warti’ah; Ahmad Afghor Fahruddin (Gotong Royong, 2025)
Community service carried out by the IAI Daruttaqwa Gresik lecturer team through leadership training activities for OSIS administrators at MA Daruttaqwa Gresik. This training aims to improve the leadership competency of students who have a strategic role in running the organization in the school environment, as well as providing an understanding of the basic concepts and practices of effective leadership. The method in this training goes through several stages, namely situation analysis, planning, implementation, and evaluation. The results of the implementation of leadership training for OSIS administrators at MA Daruttaqwa obtained a level of satisfaction of 95% of participants who stated that they were very satisfied, and 5% of participants who stated that they were quite satisfied with the overall delivery of the material. Thus, the leadership training carried out by the IAI Daruttaqwa lecturer community service team meets the expectations of the needs of the OSIS administrators of MA Daruttaqwa. Improving participants' public speaking skills in communicating with peers and teachers, increasing participants' courage in communicating and actively participating in training, participants who were previously known to be quiet and lacked confidence in expressing their opinions finally dared to speak and express ideas and thoughts openly and constructively. Participants are motivated to be more confident, become role models, and be ready to become leaders in the school environment and in society. The accompanying teachers expressed their appreciation and satisfaction for the implementation of the activity.